If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 38 = 74 Reorder the terms: 38 + 6x = 74 Solving 38 + 6x = 74 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + 6x = 74 + -38 Combine like terms: 38 + -38 = 0 0 + 6x = 74 + -38 6x = 74 + -38 Combine like terms: 74 + -38 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
| 8x^2+5x-6=0 | | 6x-(2x+5)=19 | | -4(7-2s)=11 | | 6x+31=8x+13 | | 14-9x=3x-70 | | 6x+1=26-2x | | 10x+5y=-15 | | -4(2x-10)+3=-10 | | 7(6x-3)=29 | | a^2+7ab+10b^2= | | b^3+49b= | | 10-2w=-12 | | 10-2w=12 | | 7x^2+2x-9=0 | | 2x+13=9x-8 | | 9a+4a=8a | | 4x-1=11x-42 | | 2x+22=10x-42 | | -10x+15=5x-30 | | -7(t-3)+4t=-3(-7+t) | | (-6)-5= | | (7)(-4)= | | 2x+5=7x-20 | | 2q-4+8q=7q-8+3q | | r+11+8r=11 | | (xy-420)=3x-y | | 7X-(3+2x)=X+9 | | 6(xy-420)=0 | | S=p+prt | | 3h-11=-21 | | 6(xy-420)=3x-y | | Y=-4x-7 |